“The aesthetic values of the murals of Iranian Islamic places in the Safavid era and their impact on contemporary visual environment art in Europe” - Dina Yousri Soliman Dorgham (Journal of Architecture, Art & Humanistic Science, 2023)
Research Summery : Islamic art is a strong source of inspiration for fine art through the ages, and modern art works are as close to the spirit of Islamic art in terms of concept and philosophy as possible. And Islamic art has continued with the arts of ancient and contemporary civilizations that preceded, in harmony with which the cultural identity of every society was achieved within a general framework, characterized by the tint of the Islamic spirit, which enables us to distinguish it now among thousands of artworks. But (Iran) had a great affair among the Islamic countries; As it was interested in the construction of luxurious buildings such as (mosques- palaces- mausoleums), which the Iranian artists used to beautify (plaster- stained glass- painted faience tiles), especially in decorating palaces such as (Chehel Souton Palace), and (Golestan Palace). These two palaces were a source of inspiration for the artists of post-world war II Europe; where some artists benefited from the murals of those palaces, beautified their homes and the surrounding gardens, and created beautiful mural designs inspired by Iranian Safavid art in the Islamic ear, but in a new style and artistic treatments in line with the features and characteristics of post-modern art. A new artistic style arose known as (Contemporary Visual Environment Art), and the works of some artists of this direction, such as (Fredric Attril- George Howard- Robert Vasseur...) and others, came to express the style of contemporary creativity artists, but with an ancient tradition that is similar in processed Safavid Islamic mural painting in Iran; where he used ceramic dishes and sculptural models amidst ceramic mosaics and colored glass, which the contemporary artists replaced with shells, stones and marine ores; To impart a kind of modernity and spontaneity, and thus has achieved a feature on which Islamic art is based; It is the harnessing of nature and its elements and reformulation and installation to simulate Islamic art in its various forms. Islamic art relied on showing invisible feelings, and transmitting what is visible from them, in addition to creating beauty through a comprehensive perception of the human and the universe.